When “The Show Must Go On”: Surface Acting and Deep Acting as Determinants of Emotional Exhaustion and Peer-Rated Service Delivery - Grandey, Alicia A. (Academy of Management Journal, 2003)
Affective delivery, or expressing positive emotions in service interactions, helps satisfy customers. But employees cannot always feel positive and, to avoid breaking display rules, may act. Surface acting (modifying facial expressions) and deep acting (modifying inner feelings) were tested as predictors of stress and of coworker-rated affective delivery, Consistent with a dramaturgical perspective, affective delivery ratings were negatively related to surface acting but positively related to deep acting. Surface acting, but not deep acting, was related to stress.